Razones para la guerra en la sociedad global - Senent de Frutos, Juan Antonio (2010)
In this article I develop an analysis in the context of the global society, a context split into its practical subsystems, due to the prevailing logic of confrontation and violence. Some of its expressions are studied, in the fields of international law and geopolitical relations between given societies. Also discussed are analyses of the relations between religions and cultural systems, from the perspective of mutual destruction logistics. In a context of violent interactions through diverse levels of social reality, I claim for a different strategy to guide social practices, from the recognition of universal human rights for concrete human beings, understanding that such recognition implies reducing the historical production of deaths, and the magnification of human life and of the conditions for its reproduction.